2007
DOI: 10.1038/nrmicro1595
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, diversity and ecology of aerobic CO-oxidizing bacteria

Abstract: Numerous studies indicate that carbon monoxide (CO) participates in a broader range of processes than any other single molecule, ranging from subcellular to planetary scales. Despite its toxicity to many organisms, a diverse group of bacteria that span multiple phylogenetic lineages metabolize CO. These bacteria are globally distributed and include pathogens, plant symbionts and biogeochemically important lineages in soils and the oceans. New molecular and isolation techniques, as well as genome sequencing, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
423
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(431 citation statements)
references
References 125 publications
7
423
0
1
Order By: Relevance
“…5). The form II protein appears to function as a CODH but may have a reduced capacity for CO oxidation and use an alternate substrate preferentially (15). CO utilization by S. aggregata conforms to a simple Michaelis-Menten kinetic model for low to moderate concentrations, but relatively high concentrations result in inhibition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5). The form II protein appears to function as a CODH but may have a reduced capacity for CO oxidation and use an alternate substrate preferentially (15). CO utilization by S. aggregata conforms to a simple Michaelis-Menten kinetic model for low to moderate concentrations, but relatively high concentrations result in inhibition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in differences in the classes of transport systems found in the two data sets, with COG 1462 (permease component of an ABC-transporter), COG 3090 (TRAP-type C4-dicarboxylate transport system, small permease component), COG 0025 (NhaP-type Na þ /H þ and K þ / H þ antiporters) and COG 2223 (Nitrate/nitrite transporter) being overrepresented and COG0659 (Sulphate permease and related transporters, major facilitator superfamily) being underrepresented in the sponge's bacterial community (Figure 3). Fourth, the large (COG1529) and middle (COG1319) subunits of the aerobic-type carbon monoxide dehydrogenase were overrepresented by a factor of greater than three in the sponge metagenome ( Figure 3; the small subunit (COG2080) is more abundant by a factor of 2.2, t-test, P ¼ 0.047), indicating that a portion of the sponge bacterial community can generate reductive energy from the oxidation of CO. Further analysis revealed that both form I and putative form II carbon monoxide dehydrogenase are present (King and Weber, 2007), with no apparent preference in the sponge or plankton data set (Supplementary Figure S4). Lithoheterotrophy based on CO has only been recently recognized in marine bacterioplankton (Moran and Miller, 2007), and in this study, we present evidence for a presence of this process in sponge bacteria.…”
Section: Mobile Genetic Elements and Genetic Transfermentioning
confidence: 99%
“…Genes coding for chemolithotrophic pathways known to be associated with extreme environments (Inskeep et al, 2010;Kozubal et al, 2011), including the oxidation of ferrous iron, hydrogen, arsenic, sulfur, ammonium or methane, were not found in the NAG1 assemblies. However, the NAG1 populations have two separate loci that encode aerobic carbon monoxide (CO) dehydrogenases and associated maturases (Dobbek et al, 2002;King and Weber, 2007). One locus encodes a 'Form I' CO dehydrogenase along with coxFSM and the other contains three coxL 'Form II' CO dehydrogenase sequences along with coxDEFG (Supplementary Figures S5, S6).…”
Section: Functional Analysis Of Nag1 Genome Sequencementioning
confidence: 99%